2014
DOI: 10.1039/c3fo60623f
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of jujube honey and its protective effects against chronic alcohol-induced liver damage in mice

Abstract: The antioxidant potential of jujube honey, one of the most widely consumed honeys in China, has never been determined fully. In this study, jujube honey from six geographical origins in China was analyzed for individual phenolic acid, total phenolic content, and the antioxidant effect in chronic alcohol-related hepatic disease in mice. The results showed that jujube honey from Linxian of Shanxi province contained higher phenol levels, exhibited DPPH antioxidant activity, ferric ion reducing antioxidant power (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 61 publications
(65 reference statements)
3
31
0
4
Order By: Relevance
“…MDA is the end-product of lipid peroxidation, whose levels could reflect the extent of cellular damage, serving as a marker of free radical-mediated lipid peroxidation [32]. Results shown in Figure 6 manifested that the hepatic MDA level of group II was remarkably enhanced after exposure to alcohol by 93.3%, indicating oxidative damage to the liver.…”
Section: Resultsmentioning
confidence: 99%
“…MDA is the end-product of lipid peroxidation, whose levels could reflect the extent of cellular damage, serving as a marker of free radical-mediated lipid peroxidation [32]. Results shown in Figure 6 manifested that the hepatic MDA level of group II was remarkably enhanced after exposure to alcohol by 93.3%, indicating oxidative damage to the liver.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, the effects of alcohol treatment on the levels of SOD/CAT are controversial. SOD showed an increase, no changes, or a decrease, depending on the model, diet, duration, and amount of alcohol consumption [1719]. In addition, it was reported that CAT activity decreased upon chronic ethanol consumption in a study [20].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Honey also is a good resource of antioxidants due to its abundant polyphenolic content such as flavonoids and phenolic acids. [15][16][17] Vitex negundo Linna. [11][12][13][14] Recently, the protective effects of honey on chemical oxidative liver injury has been validated by increasing researchers, making honey a potential good hepatoprotective product.…”
Section: Introductionmentioning
confidence: 99%